The Geometric Engine: Redefining Energy as the Intrinsic Work-Capacity of Spacetime - Hamidi, Nabil (My University, 2025)
Conventional physics treats energy as a property of matter, radiation, or fields embedded in spacetime. Yet recent observations—particularly from the Dark Energy Spectroscopic Instrument (DESI)—underscore evidence that what has long been attributed to a cosmological constant may instead exhibit temporal evolution. This raises deep questions about the ontological status of energy in modern physics. Here we propose a foundational reconceptualization: energy is the intrinsic ability of spacetime geometry to perform work. Reconceptualizing energy as a mechanical property of the metric itself dissolves persistent paradoxes of gravitational energy localization in general relativity and provides a structural mechanism for the observed dynamical nature of dark energy. Within this framework, energy ceases to be a substance and is instead a geometric state function of spacetime curvature and configuration.